Pengaruh Pengembangan Destinasi Wisata Terhadap Minat Kunjungan Wisatawan Pada Desa Pela Kecamatan Kota Bangun Kabupaten Kutai Kartanegara - Migi Mahendra, Dustin; Althalets, Fareis (Rifa'Institute, 2022)
Tourism is an aspect that includes a variety of interrelated matters such as human resources, natural resources and various supporting facilities which, if managed optimally, can improve the economy in a region nationally and regionally from the increasingly proclaimed tourism sector income. This study aims to examine whether there is an influence between tourist development and the 4A benchmarks, namely attractions, amenities, accessibility and ancillary on the interest of tourist visits. The type of research used is a survey with a quantitative approach. The sampling technique used is probability sampling. Data obtained by distributing questionnaires given to 100 respondents. The data analysis technique is by testing validity, reliability, followed by classical assumption test consisting of normality, heteroscedasticity and multicollinearity tests, as for multiple linear regression analysis and hypothesis testing in the form of coefficient of determination test and partial test. The results of this study indicate that attractions, amenities and ancillary have a positive effect on interest in tourist visits and accessibility has a negative effect on interest in visiting.